ANALISIS KEPUASAN PENGGUNAAN PLATFORM LEARNWISE DALAM PEMBINAAN KEWIRAUSAHAAN DI INSTITUT TEKNOLOGI INDONESIA PADA MASA PANDEMI - Mutiara Eka Puspita; Edward Sahat Tampubolon; Arrum Indriyan; Ratih Tiara Julia (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
In the new normal era, people are required to be able to adapt to new habits. Onlinemedia is an alternative for the community so that they can continue to carry outactivities, including entrepreneurship development. However, it is necessary toconduct research on the effectiveness of entrepreneurship development with onlinemedia. The Indonesian Institute of Technology is no exception. The IndonesianInstitute of Technology has a business incubator that manages entrepreneurshipcoaching using a learnwise account, an online entrepreneurship coaching platformoriginating from India. However, during the pandemic, where all coaching activitieswere carried out online, many students complained about using the platform, bothin terms of ease of use and the language used, so that the absorption of material wasslightly hampered. Based on these problems, it is necessary to evaluate how satisfiedthe use of the learnwise platform is as a solution for improving entrepreneurship development in the future. Collecting data using primary data by using aquestionnaire as a data collection tool. While the data analysis using regression withSPSS. In addition to evaluating the satisfaction of using the Learnwise platform,making learning videos using Indonesian is one of the outputs that can be done sothat the absorption of material can be maximized